1999
DOI: 10.1093/jac/43.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Ability of teicoplanin and vancomycin to induce contraction of, and histamine release from, pulmonary tissue of humans, monkeys and guinea pigs

Abstract: Amphotericin B (AmB) and fluconazole (FLU) are the major antifungal drugs used in the treatment of cryptococcosis. Both drugs are believed to exert their antifungal effects through actions on cell membrane sterols. In this study we investigated whether AmB and FLU had other, more subtle effects on C. neoformans that could contribute to their therapeutic efficacy. C. neoformans cells were grown in media with subinhibitory concentrations of either AmB or FLU and analyzed for cellular charge, phagocytosis by macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…In this way, a positive correlation between the S/V ratio of the original cells and the LHI was observed, while a negative correlation between the capsule size of heteroresistant clones and the LHI also was seen. Similar effects have been reported following the exposure of Cryptococcus neoformans to subinhibitory concentrations of fluconazole, voriconazole, amphotericin B, and terbinafine (16,21). Indeed, the S/V ratio of a cell affects several aspects of its biology, since the rate of the cell's growth depends on, among other things, the rate of nutrient exchange.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In this way, a positive correlation between the S/V ratio of the original cells and the LHI was observed, while a negative correlation between the capsule size of heteroresistant clones and the LHI also was seen. Similar effects have been reported following the exposure of Cryptococcus neoformans to subinhibitory concentrations of fluconazole, voriconazole, amphotericin B, and terbinafine (16,21). Indeed, the S/V ratio of a cell affects several aspects of its biology, since the rate of the cell's growth depends on, among other things, the rate of nutrient exchange.…”
Section: Discussionsupporting
confidence: 57%
“…These observations could be explained by the alterations in capsule (size and charge) observed in heteroresistant cells. Since cryptococcal cells are negatively charged, we hypothesized that the heteroresistance to itraconazole decreased the magnitude of the negative charge and reduced the electrostatic repulsion between the yeast cells and macrophages (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a correlation between virulence and the ergosterol synthesis pathway has been suggested previously [60]. It was reported that a pre-treatment with subinhibitory concentrations of azoles in vitro reduced cryptococcal virulence in vivo [61]. However, no difference in the susceptibility to the azole, fluconazole, which targets ERG11 in the fungal cell, was found.…”
Section: Discussionmentioning
confidence: 90%
“…For cells with irregular form, qualitative analyses were performed. The zeta potentials of the NA and A yeast cells were calculated using a zeta potential analyzer (Zetasizer NanoZS90; Malvern, United Kingdom) as described previously (39).…”
Section: Methodsmentioning
confidence: 99%